Fotografije v arhivih, knjižnicah in muzejih - Kerec, Branka (Knjižnica, 2019)
Purpose: Photographs are not usually the main type of material in archives, libraries and museums (ALM), but are normally collected in all of them. Because of different missions, each of the institutions adheres to different standards of description. As a result, different descriptions of the same material may cause difficulties in retrieval. We studied differences and similarities in the descriptions with an aim to suggest common guidelines. Methodology/approach: We took only one photograph from the University Library Maribor representing a scene from World War I. and described it in the three systems: COBISS (library), scopeArchiv (archive) and Galis (museum). The systems use the standards ISBD(NBM) and COMARC (library), ISAD(G) and ISAAR(CPF) (archive), Spectrum 5.0 and Object ID (museum). Results: ALM use the same description elements, which are important for identification. Title is transcribed or constructed. The photographer's name is controlled. Contemporary place names are standardized, old names are problematic. Recording of time may not be unified in the same institution. The motif may remain different, because each institution may be interested in different details. The location data record the storage of the photo and are quite similar in ALM. The relationship between the original and digitized photo remains unsolved. Research limitations: We created a hypothetical, idealistic description of only one photograph in the three systems. Originality/practical implications: One particular photograph was described in three institutions, i.e. an archive, a library and a museum. The descriptions were created by experienced practitioners from these institutions.
Keywords: arhivi; bibliografski opisi; fotografija; katalogizacijska pravila; knjižnice; muzeji